ANALYSIS OF SHARIA UMKM DEVELOPMENT STRATEGIES IN THE DIGITAL ECONOMY ERA (STUDY ON HNI-HPAI BC MEDAN 8) - Adinda Khairunisa Ahmadi; Rasta Kurniawati Br Pinem (RADJA PUBLIKA, 2026)
This study aims to analyze the development strategy of Sharia-based Micro, Small, and Medium Enterprises (MSMEs) in the digital economy era at HNI-HPAI BC Medan 8. The study uses a qualitative approach with the Miles and Huberman interactive model data analysis method which includes the stages of data collection, data reduction, data presentation, and drawing conclusions. Data collection techniques are carried out through interviews, observation, and documentation, while data validity is tested using triangulation of sources, techniques, and observers. The research results show that the development strategy for sharia-compliant MSMEs is implemented through the integration of sharia principles and digital technology. The implementation of sharia principles is reflected in product halal assurance, price transparency, and the avoidance of riba (usury ), gharar (gharar ), and maisir (gambling) . Meanwhile, the use of digital technology through the HNI.id platform and social media has proven effective in expanding market reach and increasing customer base. However, challenges remain, including the perception of relatively high product prices and low consumer understanding of the importance of halal and quality products. This research implies that the successful development of Sharia-compliant MSMEs depends not only on the use of digital technology but also on the consistent application of Sharia principles and the ability to build consumer trust. Therefore, market education strategies and policy support are needed to improve digital and halal literacy to promote the sustainability of Sharia-compliant MSMEs in the digital economy era.